Connecting City and Countryside? Faces of Cycling Mobility in Belgium, 1890-1914. (1st November 2013) - Knuts, Stijn; Delheye, Pascal
<x xml:space="preserve">Abstract</x> Focusing on Belle Époque Belgium, this paper analyses the changes the advent of cycling and its new mobility engendered in the sociocultural dialectics between city and countryside. By studying the interwoven, often contradictory motivations behind and representations of bicycle use, an attempt is made to determine the factors leading to cyclists' cultural imagining of both city and countryside, how this was shaped in discourse and practice and how this evolved under the influence of the bicycle's shifting social connotations after 1900. We focus especially on organized forms of Belgian cycling such as urban cycling clubs and national cycling associations.